The identification of genes from the oyster Crassostrea gigas that are differentially expressed in progeny exhibiting opposed susceptibility to summer mortality. - Huvet, Arnaud; Herpin, Amaury; Degremont, Lionel; Labreuche, Yannick; Samain, Jean-François; Cunningham, Charles (Gene, 2004)
International audience Summer mortality associated with juveniles of the oyster Crassostrea gigas is probably the result of a complex interaction between the host, pathogens and environmental factors. Genetic variability in the host appears to be a major determinant in its sensitivity to summer mortality. Previously, divergent selection criteria based on summer survival have been applied to produce oyster families with resistant and susceptible progeny. In this paper, we describe the use of suppression subtractive hybridization to generate 150 C. gigas clones that were differentially regulated between resistant and susceptible F2 progeny. The nucleotide sequence of these clones was determined. In 28%, the inferred amino sequence was found to match the products of known genes, 14% matched hypothetical proteins and a further 14% appeared to contain open reading frames (ORFs) whose product had no obvious homologue in the nucleotide databases. It has been hypothesized that differences exist in the level of energy generation and immune function between resistant and susceptible progeny. In light of this, clones encoding homologues of cavortin, cyclophilin, isocitrate dehydrogenase, sodium glucose cotransporter, fatty acid binding protein, ATPase H+ transporting lysosomal protein, precerebellin, and scavenger receptor were analyzed by real-time PCR. These transcripts were induced in resistant progeny when compared to their susceptible counterparts. A bacterial challenge of oysters resulted in the suppression of six of these transcripts in only those that were resistant to summer mortality. This study has identified potential candidates for further investigation into the functional basis of resistance and susceptibility to summer mortality.